(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Iraq suffers from multiple environmental problems, so it is considered one of the five countries most vulnerable to desertification and climate change in the world. It suffers from a significant shortage of water and its quality, low rainfall rates, higher temperatures than normal, especially in the winter, and air pollution. As a result of high levels of carbon and other polluting gases. Therefore, these major environmental problems and challenges necessitate Iraq to take real, tangible steps and policies based on well-studied and clear scientific foundations towards reducing these environmental problems and challenges. Renewable energy is one of the important means and tools that work to reduce emissions of harmful gases, especially gas monoxide, carbon dioxide, and methane resulting from fossil fuels as a result of burning them in the air or during their extraction. Renewable energy is a clean, sustainable, and environmentally friendly energy, and its use is consistent with Sustainable development goals and agenda 2023. Iraq produces an average of 4,423 thousand barrels of oil equivalent per day, most of which are from fossil fuels, especially crude oil, and consumes an average of 1,214 thousand barrels of oil equivalent per day. Renewable energy production or consumption constitutes only 14 thousand barrels of oil equivalent per day, constituting a percentage of 1.15% of the total. Energy consumption, which shows the extent of Iraq’s heavy dependence on fossil fuels to meet local demand, and this has major negative effects on the environment, which already suffers from multiple problems. The research aims to analyze energy production and consumption in Iraq and its repercussions on the local environment, and analyze local energy policies and the extent of their realism and consistency with the requirements of this stage in light of the rapid global changes in the field of energy. Then propose appropriate policies and procedures to mitigate the country’s environmental problems.